Perceptual Training Prevents the Emergence of the Other Race Effect during Infancy - Heron-Delaney, Michelle; Anzures, Gizelle; Herbert, Jane S.; Quinn, Paul C.; Slater, Alan M.; Tanaka, James W.; Lee, Kang; Pascalis, Olivier (PLOS ONE, 2011)
Experience plays a crucial role in the development of the face processing system. At 6 months of age infants can discriminate individual faces from their own and other races. By 9 months of age this ability to process other-race faces is typically lost, due to minimal experience with other-race faces, and vast exposure to own-race faces, for which infants come to manifest expertise [1]. This is known as the Other Race Effect. In the current study, we demonstrate that exposing Caucasian infants to Chinese faces through perceptual training via picture books for a total of one hour between 6 and 9 months allows Caucasian infants to maintain the ability to discriminate Chinese faces at 9 months of age. The development of the processing of face race can be modified by training, highlighting the importance of early experience in shaping the face representation.